2019
DOI: 10.1021/acs.macromol.9b00073
|View full text |Cite
|
Sign up to set email alerts
|

Semiaromatic Poly(thioester) from the Copolymerization of Phthalic Thioanhydride and Epoxide: Synthesis, Structure, and Properties

Abstract: We report a new semiaromatic poly­(thioester) obtained through the copolymerization of phthalic thioanhydride and propylene oxide. The reaction was catalyzed by a chromium-based complex in conjunction with [PPN]­Cl, where PPN = bis­(triphenyl­phosphine)­iminium. The reaction temperature exerted a critical influence over catalytic activity as well as the structure of the resulting polymer chain. NMR spectroscopy revealed that the resultant copolymers contained multiple repeating units, including thioester, este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 41 publications
(54 reference statements)
0
57
1
Order By: Relevance
“…Very recently the sulphur analogues of anhydride/epoxide ROCOP were reported to deliver poly(thioester) structures inaccessible by conventional routes. [191][192][193] Figure 29: ROCOP of thioanhydride with epoxides or thiiranes.…”
Section: Rocop Of Thioanhydrides With Epoxides or Thiiranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently the sulphur analogues of anhydride/epoxide ROCOP were reported to deliver poly(thioester) structures inaccessible by conventional routes. [191][192][193] Figure 29: ROCOP of thioanhydride with epoxides or thiiranes.…”
Section: Rocop Of Thioanhydrides With Epoxides or Thiiranesmentioning
confidence: 99%
“…Phthalic thioanhydride (PTA)/PO ROCOP using Cr III ‐salen/PPNCl catalysts showed good performance (TOF 30–1420 h −1 , 25–100 °C, 0.1–0.001 mol %, M n =18.2–60.1 kg mol −1 ) [192] . The polymer contained thioester, ester, and thioether linkages, was regio‐random, and lacked long‐range order.…”
Section: Rocop Of Thioanhydrides With Epoxides or Thiiranesmentioning
confidence: 99%
“…Yet ring-opening a highly strained epoxide is an easier target than LA, [30][31][32] a phenomenon that has successfully been exploited in various polymerisations. [33][34][35][36][37][38] Thomas, Maron et al demonstrated that the Jacobsen (salen)AlCl complex can initiate LA ROP via epoxide ringopening (Figure 1, left) in the presence of an onium salt (PPNCl) and excess epoxide. [39] We recently showed that external Lewis bases can be avoided by incorporating electron-donating diaminosubstituents into the salen scaffold (Figure 1 right).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently,t he sulfur analogues of anhydride/ epoxide ROCOP were reported to deliver poly(thioester) structures inaccessible by conventional routes. [191][192][193] Lu and co-workers reported ROCOP of thiiranes with stearic (STA) or glutaric thioanhydride (GTA) using Lewis base/PPNX catalysts (Figure 29). [191] Them ost effective was PPNOAc, which delivered polymers quickly with molar masses close to theoretical expectations (TOF 787 h À1 ,2 5 8 8C, 0.4 mol %, M n = 53.6 kg mol À1 ,for STA/PS;F igure 30).…”
Section: Rocop Of Thioanhydrides With Epoxides or Thiiranesmentioning
confidence: 99%
“…Phthalic thioanhydride (PTA)/PO ROCOP using Cr IIIsalen/PPNCl catalysts showed good performance (TOF 30-1420 h À1 ,2 5-100 8 8C, 0.1-0.001 mol %, M n = 18.2-60.1 kg mol À1 ). [192] Thep olymer contained thioester,e ster, and thioether linkages,w as regio-random, and lacked longrange order.T he linkage scrambling was attributed to intramolecular and/or intermolecular transesterification reactions akin to CS 2 /epoxide ROCOP.S crambling increased with temperature and influenced the polymersg lass transition temperature (T g = 62 8 8Cf rom reactions at 100 8 8C, T g = 70 8 8C from reactions at 25 8 8C, both with M n % 18 kg mol À1 ). A tethered Lewis base/Cr III -salen catalyst showed fewer transesterifications (TOF 94-567 h À1 ,0 .1-0.01 mol %, 25-70 8 8C, M n = 15.9-49.7 kg mol À1 ).…”
Section: Rocop Of Thioanhydrides With Epoxides or Thiiranesmentioning
confidence: 99%